The Implementation Of The SAS Method With Picture Card Activities To Enhance Initial Reading Abilities - Komang Astrini Widita Mahayasih; Pramesti Pradna Paramita (Eduvest - Journal of Universal Studies, 2024)
This study examines the case of two students, Y.A.A and R, both experiencing difficulties in reading, potentially indicating learning disorders or intellectual disabilities. Y.A.A, a 13-year-old boy, struggles with reading despite being active in other activities. R, on the other hand, shows signs of malnutrition during childhood and has difficulty in various academic subjects. Assessments using the WISC and VSMS indicate below-average intellectual abilities and social-communication skills. Informal reading tests reveal R's challenges in identifying letters, pronouncing words, and comprehending text. Cognitive, socio-emotional, and motivational aspects contribute to R's reading difficulties, suggesting a need for tailored interventions. The Synthetic Analysis Structure (SAS) method is proposed to improve R's reading skills, supported by psychoeducation for R's family and teachers. Evaluation shows promising progress in R's reading ability and emphasizes the importance of personalized interventions and parental involvement.